Moving toward a better understanding of the experience and measurement of breastfeeding-related pain - Kimberley T. Jackson; Sheila O'Keefe-McCarthy; Tara Mantler (Taylor & Francis Group, 2019)
Purpose: Despite how commonly breastfeeding-related pain is experienced in the postpartum period, and its frequent implication in breastfeeding cessation, this unique type of pain is not well evaluated nor assessed. The purpose of this study was to gain a comprehensive description and understanding of breastfeeding-related pain among postpartum breastfeeding women. Methods: This study employed a mixed methods approach using a descriptive-interpretive qualitative approach, in addition to administering the Short-Form McGill Pain Questionnaire, second version, to comprehensively gain both quantitative and qualitative descriptors of breastfeeding-related pain. Fourteen partnered and educated women living in Southern Ontario with experience of breastfeeding-related pain took part in this study. Results: The results from this study suggest that breastfeeding-related pain is often experienced as severe and distressing, and comprises various elements of pain including continuous, intermittent, neuropathic, and affective components. Conclusion: Breastfeeding-related pain is multidimensional and can be severe and distressing for women. Current measurement tools may not adequately reflect the multidimensional components of this unique type of pain, which may limit the effectiveness of health care providers to help with its identification and management.